2017
DOI: 10.1186/s12910-017-0231-8
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making on therapeutic futility in Mexican adolescents with cancer: a qualitative study

Abstract: BackgroundThe world literature shows that empirical research regarding the process of decision-making when cancer in adolescents is no longer curable has been conducted in High-income, English speaking countries. The objective of the current study was to explore in-depth and to explain the decision-making process from the perspective of Mexican oncologists, parents, and affected adolescents and to identify the ethical principles that guide such decision-making.MethodsPurposive, qualitative design based on indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(87 citation statements)
references
References 22 publications
0
87
0
Order By: Relevance
“…8,32,33 Other factors, including a patient's age, family/cultural ethnicity and preferences, discipline of health care provider, and type of treatment center, may also further influence AYA patients' overall experiences of end-of-life care. 8,[34][35][36] One qualitative study of Mexican oncologists highlighted that they preferred to broach end-of-life topics only once they had determined curative treatment options had been unsuccessful. 34 Although little research has explored this, the timing of these conversations may also vary between diagnosis groups; one article reported that end-of-life discussion for North American AYAs with leukemia/lymphoma was more likely to occur in the last seven days of life, compared to patients with either a solid tumor (89 days) or central nervous system/brain tumor diagnoses (37 days).…”
Section: Conversation Timingmentioning
confidence: 99%
See 4 more Smart Citations
“…8,32,33 Other factors, including a patient's age, family/cultural ethnicity and preferences, discipline of health care provider, and type of treatment center, may also further influence AYA patients' overall experiences of end-of-life care. 8,[34][35][36] One qualitative study of Mexican oncologists highlighted that they preferred to broach end-of-life topics only once they had determined curative treatment options had been unsuccessful. 34 Although little research has explored this, the timing of these conversations may also vary between diagnosis groups; one article reported that end-of-life discussion for North American AYAs with leukemia/lymphoma was more likely to occur in the last seven days of life, compared to patients with either a solid tumor (89 days) or central nervous system/brain tumor diagnoses (37 days).…”
Section: Conversation Timingmentioning
confidence: 99%
“…8,[34][35][36] One qualitative study of Mexican oncologists highlighted that they preferred to broach end-of-life topics only once they had determined curative treatment options had been unsuccessful. 34 Although little research has explored this, the timing of these conversations may also vary between diagnosis groups; one article reported that end-of-life discussion for North American AYAs with leukemia/lymphoma was more likely to occur in the last seven days of life, compared to patients with either a solid tumor (89 days) or central nervous system/brain tumor diagnoses (37 days). 8 This disparity may have been driven by differences in treatment options and corresponding prognostic uncertainty.…”
Section: Conversation Timingmentioning
confidence: 99%
See 3 more Smart Citations